Global Prevalence of Periodontal Disease and Lack of Its Surveillance - Muhammad Nazir; Asim Al-Ansari; Khalifa Al-Khalifa; Muhanad Alhareky; Balgis Gaffar; Khalid Almas (The Scientific World Journal)
Background. Periodontal disease is a public health problem and is strongly associated with systemic diseases; however, its worldwide distribution is not fully understood. Objective. To evaluate global data of periodontal disease: (1) among adolescents, adults, and older population and (2) in low-, middle-, and high-income countries. Methods. This ecological study included data of periodontal disease from the World Health Organization’s data bank which are based on the Community Periodontal Index of Treatment Needs (CPITN code: 0 = no disease; 1 = bleeding on probing; 2 = calculus; 3 = periodontal pocket (PD) 4-5 mm; 4 = PD (6+ mm). Age- and income-related periodontal disease inequalities were evaluated across the globe. Results. Compared with 9.3% of adults and 9.7% of older persons, 21.2% of adolescents had no periodontal disease (P=0.005). Nearly 18.8% of adolescents compared with 8.9% of adults and 5% of older persons had bleeding on probing (P≤0.001). Similarly, 50.3% of adolescents, 44.6% of adults, and 31.9% older persons demonstrated the occurrence of calculus (P=0.01). On the other hand, older persons had the highest prevalence of PD 4-5 mm and PD 6+ mm than adults and adolescents (P≤0.001). The distribution of periodontitis (CPITN code 3 + 4) in adults differed significantly in low- (28.7%), lower-middle- (10%), upper-middle- (42.5%), and high-income countries (43.7%) (P=0.04). However, no significant differences in periodontitis (CPITN code 3 + 4) were observed in adolescents and older persons in low- to high-income countries. Conclusions. Within the limitations of data, this study found that the distribution of periodontal disease increases with age. Periodontitis was the most common in older persons and in population from high-income countries.